Art day by day : 366 brushes with history - Johnson, Alex, 1969- (Thames and Hudson, 2021)
Art Day by Day' presents snapshots of the most exciting, unusual and noteworthy art events from around the world and throughout history through direct testimonies, eyewitness accounts and contemporary chroniclers. Each day has its own section, starting with an extended quote giving artists, critics and commentators their voice to speak directly to us, followed by a brief explanatory text, and ending with other important events in art on that day e.g. births, deaths and exhibition openings. Not every entry is momentous, but all are significant. Yes, there are thefts, murders, artistic mishaps and eureka moments, but there are also more relatable episodes such as President Theodore Roosevelt's doodles, Michelangelo writing to his nephew about his kidney stones and Monet getting the green light for his water garden. Every day has a story to tell.